Kandungan Protein, lemak dan Kolesterol Daging Rusa Timor (Cervus timorensis) di Pasar Traditional Wamanggu - Desmina Kristiani Hutabarat; Sola Gracia; Nurcholis Nurcholis; Syetiel Maya Salamony; Apri Irianto (Faculty of Agriculture, Musamus University, 2024)
This research aimed to determine deer meat's protein, fat, and cholesterol content in the Wamanggu Merauke Traditional market. The procedure for this research is to buy deer meat from the Wamanggu Traditional Market at four different points, and the sampling process is carried out randomly without selecting specific parts of the deer carcass with the purchase amount for each place being 500g with sample code (S1, S2, S3, S4 ). The parameters observed in the deer meat quality test are Protein, fat, and cholesterol. The research showed that deer meat had a protein content of 22.77%, a fat content of 4.73%, and a cholesterol content of 31.23mg. This research concludes that deer meat's quality of protein, fat, and cholesterol in the Wamanggu market is good.